2010
DOI: 10.3109/10641955.2010.484083
|View full text |Cite
|
Sign up to set email alerts
|

Phosphodiesterase Inhibitor Effect on Small Artery Function in Preeclampsia

Abstract: Acute effects may have been lost as sildenafil administration occurred many hours prior to myography. Plasma sildenafil levels may have been lower than required for vascular response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 15 publications
0
8
0
1
Order By: Relevance
“…Interestingly, recent studies have shown that sildenafil can be used successfully to correct a thin endometrium and reduce recurrent implantation failure (15,16), and therapeutically for intrauterine growth restriction (IUGR) and pre-eclampsia (17,18). Others have refuted the suggested benefits of sildenafil as a treatment for preeclampsia (19,20), but the intervention might have been applied too late to reverse endothelial damage and placental dysfunction. Recent studies have examined therapeutic interventions for the treatment of preeclampsia in a high-risk population, based on dietary supplementation with L-arginine in food bars, and antioxidant vitamins (21).…”
mentioning
confidence: 95%
“…Interestingly, recent studies have shown that sildenafil can be used successfully to correct a thin endometrium and reduce recurrent implantation failure (15,16), and therapeutically for intrauterine growth restriction (IUGR) and pre-eclampsia (17,18). Others have refuted the suggested benefits of sildenafil as a treatment for preeclampsia (19,20), but the intervention might have been applied too late to reverse endothelial damage and placental dysfunction. Recent studies have examined therapeutic interventions for the treatment of preeclampsia in a high-risk population, based on dietary supplementation with L-arginine in food bars, and antioxidant vitamins (21).…”
mentioning
confidence: 95%
“…In addition, a dose escalation design meant over half of the women received only the lowest dose of 20 mg three times a day (TDS). No difference was found in the vascular reactivity of myometrial vessels from women receiving sildenafil compared with placebo, possibly because of the interval between the last dose and delivery …”
Section: How Can We Treat Poor Placentation?mentioning
confidence: 93%
“…The same group performed a parallel study in which they used pressure myography to analyze the relaxation of the arteries extracted from the umbilical cord and the omentum of the study subjects. They found no difference between groups, showing that the drug had no effect on ex vivo samples [60].…”
Section: T H E U S E O F S C a T T H E O N S E T O F P R E E C L A M mentioning
confidence: 96%